Exploring translanguaging as a pedagogical strategy used by the english teacher in EFL classroom setting - Riswanto Riswanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Translaguaging is a practice in which educators allow the mixing of languages in a bilingual educational setting which can be employed to create an engaged and conducive learning environment. This study aims to analyze the application of translanguaging by English teachers as a pedagogic strategy in learning English. The aim is to find out how the translanguaging technique is used by the teacher in teaching English, and what the impact is obtained from the use of translanguaging in learning English. This research was conducted at SMAN 3 Bengkulu Selatan and the participants were one English teacher and 27 students, namely class XI MIPA I. This research employed a qualitative descriptive study, and data collection techniques were interviews and checklist observations. The findings of this study revealed that teachers employed three techniques in translanguaging when teaching English, and the impact obtained from using translanguaging was positive, including students becoming easier to understand what the teacher is saying, students being more active in responding to teachers, and students' English language skills get better. The authors hope that this method can be applied effectively and according to the needs of students.